Radiation Exposure in Posterior Lumbar Fusion: A Comparison of CT Image-Guided Navigation, Robotic Assistance, and Intraoperative Fluoroscopy. Issue 4 (May 2021) - Wang, Erik; Manning, Jordan; Varlotta, Christopher G.; Woo, Dainn; Ayres, Ethan; Abotsi, Edem; Vasquez-Montes, Dennis; Protopsaltis, Themistocles S.; Goldstein, Jeffrey A.; Frempong-Boadu, Anthony K.; Passias, Peter G.; Buckland, Aaron J.
Study Design: Retrospective clinical review. Objective: To assess the use of intraoperative computed tomography (CT) image-guided navigation (IGN) and robotic assistance in posterior lumbar surgery and their relationship with patient radiation exposure and perioperative outcomes. Methods: Patients ≥18 years old undergoing 1- to 2-level transforaminal lateral interbody fusion in 12-month period were included. Chart review was performed for pre- and intraoperative data on radiation dose and perioperative outcomes. All radiation doses are quantified in milliGrays (mGy). Univariate analysis and multivariate logistic regression analysis were utilized for categorical variables. One-way analysis of variance with post hoc Tukey test was used for continuous variables. Results: A total of 165 patients were assessed: 12 IGN, 62 robotic, 56 open, 35 fluoroscopically guided minimally invasive surgery (MIS). There was a lower proportion of women in open and MIS groups ( P = .010). There were more younger patients in the MIS group ( P < .001). MIS group had the lowest mean posterior levels fused ( P = .015). Total-procedure radiation, total-procedure radiation/level fused, and intraoperative radiation was the lowest in the open group and highest in the MIS group compared with IGN and robotic groups (all P < .001). Higher proportion of robotic and lower proportion of MIS patients had preoperative CT ( P < .001). Estimated blood loss ( P = .002) and hospital length of stay ( P = .039) were lowest in the MIS group. Highest operative time was observed for IGN patients ( P < .001). No differences were observed in body mass index, Charlson Comorbidity Index, and postoperative complications ( P = .313, .051, and .644, respectively). Conclusion: IGN and robotic assistance in posterior lumbar fusion were associated with higher intraoperative and total-procedure radiation exposure than open cases without IGN/robotics, but significantly less than MIS without IGN/robotics, without differences in perioperative outcomes. Fluoro-MIS procedures reported highest radiation exposure to patient, and of equal concern is that the proportion of total radiation dose also applied to the surgeon and operating room staff in fluoro-MIS group is higher than in IGN/robotics and open groups.